(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study introduces the design and performance analysis of a biradial turbine optimized for application in Oscillating Water Column (OWC) systems. The proposed turbine features a symmetric structure relative to a plane perpendicular to the rotational axis, with guide vanes positioned at regular intervals around the axis to effectively control flow direction. Numerical simulations were performed to investigate the influence of guide vane angle variations (21°, 30.8°, 48.5°, 50°) on turbine performance, considering multiple design cases. The results of the numerical analysis demonstrate that the turbine efficiency (η) increases with the flow coefficient (Φ), peaking at 0.78 within the Φ ≈ 0.1–0.15 range, followed by a gradual decline. In the lower range (Φ ≈ 0.05–0.1), Case 1 and Case 2 exhibited lower efficiency than the reference design, while in the Φ ≈ 0.1–0.15 range, these cases achieved up to a 4% improvement over the reference. Notably, larger guide vane angles (48.5°, 50°) extended the range of maximum efficiency, indicating enhanced flow control capabilities. Case 3 consistently outperformed or matched the reference efficiency across all ranges, highlighting its potential as an optimal design. The numerical predictions showed strong agreement with experimental data, with deviations within ±2%, thereby validating the reliability of the computational model. This research presents a novel approach to biradial turbine design, distinguishing it from conventional radial and axial turbines, and demonstrates its capability to enhance energy conversion efficiency in OWC systems. The findings provide valuable insights for the optimization of turbine designs in wave energy applications.